“Wir schaffen das”: o refúgio atual na Alemanha sob a luz da acolhida humanitária da Cruz Vermelha - Zola, Juliê Makumbi Pontes (2021)
The present text of the Master's thesis of the Postgraduate Program in Social Sciences brings an intertwining of studies in the area of Anthropology and International Relations, having as thematic proposal the refuge in contemporaneity and humanitarian assistance. It uses the analysis of the performance of the German Red Cross Kappler Knoten center in the city of Freiburg to reflect on the relevance of non-governmental humanitarian relief organizations in the current context of refuge in Germany. It assumes that the globalized era is ambiguous, as it promoted the encounter between different societies around the global economic, political and social dynamics, but at the same time, it accentuated local differences and divided peoples according to their productive and its cultural attributes. The result of this was political crises, wars for power and, above all, the search for refuge. In this sense, the question that guides the research is: why is the action of non-governmental organizations such as the Kappler Knoten dormitory at DRK: Flüchtlingssozialdienst in Freiburg necessary for the reception and inclusion of contemporary refugees in Germany? The work in its totality aims to identify and analyze how the Red Cross center, known as Kappler Knoten in the city of Freiburg, acts in the process of welcoming the current refugee into German society. This is best portrayed in the specific objectives, which show that reception involves the displaced person, the State that receives and the society that welcomes them. For this, the qualitative research was developed using the inductive method, using several procedures, such as documental research, participant observation, semi-structured interviews and virtual ethnography when the field became inaccessible as a result of the COVID-19 pandemic. Through this research, it was observed that there is a demand from the State, the refugee and society in relation to humanitarian relief, with particular aspects, but which legitimizes the performance of non-governmental bodies such as the Kappler Knoten center in Freiburg. It is concluded that the current German context is subject to certain changes of a political nature, which may have an impact on humanitarian reception. However, despite an uncertain near future, and other changes already present, non-governmental bodies play an important role in reception, education and inclusion of refugees and asylum seekers in the social environment of contemporary Germany.